Analysis of Base And Non-Base Sectors in The Economic Development of Jayawijaya Regency - Silas Tanggu Redu; Vedrix Vernanda; Agus Sumaryadi (SOCA: Jurnal Sosial Ekonomi Pertanian, 2023)
Jayawijaya Regency is the economic center for the central mountainous region in Papua Province. As an economic center, there is a growing gap between economic sectors, uneven income distribution, and a very high poverty rate in Jayawijaya Regency. Therefore, this research was conducted with the aim of 1) knowing the base and non-base economic sectors in the economic development of Jayawijaya Regency, and 2) knowing the projected changes and competitive advantages of the Jayawijaya Regency economic sectors. The location of the study is determined purposively. The data type is secondary data in the form of Gross Regional Domestic Product (GRDP) of Jayawijaya Regency at 2010 Constant Market Prices by Industry for the period 2010-2019. The source of the data comes from BPS (Berau Central of Statistics) Jayawijaya Regency and Papua Province. The data were analyzed using LQ and DLQ analysis methods. The results showed that there are 15 base or superior economic sectors and 2 non-base or potential economic sectors from 17 economic sectors in Jayawijaya Regency. Non-base economic sectors are the mining and quarrying industry; and water supply, sewerage, waste management and remediation activities. Projections of changes and competitive advantages of the economic sector show that repositioning occurs in the water supply, sewerage, waste management and remediation activities, while the mining and quarrying industries have not undergone changes with low competitiveness